Closed-loop interaction with the cerebral cortex: a review of wireless implant technology§. Issue 3 (3rd July 2017) - Kohler, Fabian; Gkogkidis, C. Alexis; Bentler, Christian; Wang, Xi; Gierthmuehlen, Mortimer; Fischer, Joerg; Stolle, Christian; Reindl, Leonhard M.; Rickert, Joern; Stieglitz, Thomas; Ball, Tonio; Schuettler, Martin
Abstract: Wireless implants for interaction with the cortex have developed rapidly over the last decade and increasingly meet demands of clinical brain–computer interfaces. For such applications, well-established technologies are available, suitable for recording of neural activity at different spatial scales and adequate for modulating brain activity by cortical electrical stimulation. The incorporation of recording and stimulation into closed-loop systems is a major aim in active, fully implantable medical device design. To reduce clinical long-term implantation risk and to increase the spatial specificity of epicortical recordings and stimulation, micro-electrocorticography is a promising technology. However, currently there is a lack of implants suitable for chronic human clinical applications that utilize micro-electrocorticography and possess closed-loop functionality. Here, we describe the clinical importance of cortical stimulation, give an overview of existing implants that use mainly epicortical recording methods, and present results of a closed-loop micro-electrocorticography system developed for clinical application within a collaborative framework. Finally, we conclude with our vision of future design options in the field of neuroprosthetic devices.